The functional morphology of the metapleural gland of the leaf-cutting ant Atta laevigata (Formicidae: Attini) - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Given the importance of the metapleural gland in ants, the present study aimed at describing it in minor, media, and major workers of Atta laevigata, focusing their physiology using scanning electron microscopy (SEM), histologic, and histochemical techniques. The results revealed that this gland is paired and located in the metathoracic region, consisted of two portions: secretory and the storage ones. Both portions are connected by extracytoplasmic canaliculi that drain the secretion of each secretory cell they form groups that open into the perforated plate located in the wall of the collecting chamber. The oval-shaped and elongated secretory cells form clusters of approximately 20 cells, bundled together by connective tissue. Each secretory cell connects to the reservoir through a canaliculus divided into an intra- and extracytoplasmic portion. The collecting chamber and the reservoir are internally lined by a single squamous epithelium with a cuticular intima, with folds in the collecting chamber and smooth in the remaining of the reservoir. External muscle layers surrounding the reservoir are observed which aid the release of secretion by the gland opening (one on each side) located in the exoskeleton near coxae of hind legs. Secretory cells were strongly positive for acidic and total lipids, proteins, and acidic polysaccharides, suggesting the glycolipoproteins nature of the final secretion. Morphometrically, the diameter of the reservoir is proportional to body size of minor, media, and major workers. This implies a larger capacity to produce secretion, including antibiotic substances, by the individuals that perform specific tasks within the colony. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Atta laevigata; Attini; Metapleural gland; Secretory cells